Glycerol and natural sugar‐derived complex modulate differentially stratum corneum water‐binding properties and structural parameters in an in vitro Raman‐desorption model. Issue 1 (11th October 2022) - Fluhr, Joachim W.; Tfayli, Ali; Darlenski, Razvigor; Darvin, Maxim E.; Joly‐Tonetti, Nicolas; Lachmann, Nadège
Abstract: The epidermal protective functions are closely associated with skin hydration homeostasis. The understanding of different states of water binding is a rising concept in assessing topically applied formulations and their interaction within the stratum corneum (SC). In addition to global water content, primary bound water, partially bound water, and unbound water and barrier‐related lipid lateral packing and protein secondary structure can be measured by Raman spectroscopy. This study aimed to establish an in vitro SC model to evaluate differences in the efficacy of a natural sugar‐derived complex in combination with glycerol and a botanical extract in modulating SC water binding and structural proteins and barrier lipids. These compounds were selected due to their water‐binding and soothing properties. The SC water profiles were assessed at the surface and in 8 μm SC depth. After a 12‐hour hyperhydration and subsequent product incubation the measurements were performed during a 6 hours desiccation phase. The maximal water caption and the time until reaching a steady state are measured as well as water retention and resistance against water loss. Global water content, partially bound, and unbound water, as well as lipid and protein structures were assessed with confocal Raman microspectroscopy. Both the natural sugar‐derived mixture and more pronounced, the same mixture with additional glycerol increased all three water‐binding parameters at the surface and in 8 μm SC depth at the beginning and during the desiccation phase. Further addition of botanical extract did not result in an additional increase of the water‐binding. All three formulations showed an increase in the lipid lateral packing values prevented the protein alteration as measured by β‐sheets signal compared to blank. The present model is suited for screening studies comparing the specific effects of different compounds on hydration states. The natural sugar‐derived mixture Aquaxyl showed evidence for an improvement of all SC hydration states, lipid and protein structure which was further enhanced by the addition of glycerol 5%. This improvement was evidenced at the surface and within the SC for all hydration‐related parameters, and the lipid as well the protein structures. The addition of botanical extract phytoessence blue daisy did not show further improvement. Abstract : Schematic Raman‐desorption process over 6 hours: Global water content (vOH/vCH) with an initial exposure to 100% relative humidity (RH) (blue arrow) followed by product incubation (blue bar). At the end of the pre‐treatment period, the desiccation process started (orange bar). The desiccation phase starts at point 1 going into the desiccation phase until reaching a steady state at point 2. Point 1 represents the water caption at 100% RH. Point 2 is delayed in reaching the steady‐state if water‐binding components are applied to the SC indicating water retention and increased resistance against water loss. The plateau 3 represents the amount of water holding capacity of the SC over several hours.